2014
DOI: 10.4103/0971-4065.133005
|View full text |Cite
|
Sign up to set email alerts
|

Fungal peritonitis in continuous ambulatory peritoneal dialysis: The impact of antifungal prophylaxis on patient and technique outcomes

Abstract: Fungal peritonitis (FP) is a rare, but serious complication of peritoneal dialysis. We analyzed the incidence of FP, associated risk factors and outcome of patients with FP and evaluated the role of prophylactic antifungal agent in reducing its incidence. We studied all patients with FP from January 2005 to January 2012. Study period was divided into two parts, period I (January 2005 to January 2010), when prophylactic antifungal was not used and period II (January 2010 to January 2012), when prophylactic anti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…Unfortunately, nystatin is not available in some countries. Observational data 118 120 and one randomised controlled trial 122 showed that prophylactic fluconazole is effective. The randomised controlled trial of oral fluconazole included patients who received antibiotics for treating exit-site and tunnel infection, in addition to the treatment of peritonitis 122 .…”
Section: Prevention Of Peritonitismentioning
confidence: 99%
See 1 more Smart Citation
“…Unfortunately, nystatin is not available in some countries. Observational data 118 120 and one randomised controlled trial 122 showed that prophylactic fluconazole is effective. The randomised controlled trial of oral fluconazole included patients who received antibiotics for treating exit-site and tunnel infection, in addition to the treatment of peritonitis 122 .…”
Section: Prevention Of Peritonitismentioning
confidence: 99%
“…The majority of fungal peritonitis episodes are preceded by courses of antibiotics. [109][110][111][112] A number of observational studies [113][114][115][116][117][118][119][120] and randomised trials 121,122 have examined the use of either oral nystatin (500,000 units qid) or fluconazole (200 mg every 48 h) as prophylaxis during antibiotic therapy. In essence, two randomised control trials 121,122 and a systematic review 43 showed a significant benefit.…”
Section: Secondary Preventionmentioning
confidence: 99%
“…Unfortunately, nystatin is not available in some countries. Observational data and 1 randomized controlled trial showed that prophylactic fluconazole is effective ( 197 200 ). However, there are potential problems (e.g.…”
Section: Prevention Of Peritonitismentioning
confidence: 99%
“…The association of fungal infection to this procedure have been shown repeatedly in the literature on peritonitis in adult [7,[20], [21], [22]] and children [23], mostly caused by Candida species. Fungi commonly are involved in biofilm formation on indwelling and prosthetic materials, interfering with eradication the infection [22]. Therefore, after final diagnosis the catheter as likely source of infection was removed.…”
Section: Discussionmentioning
confidence: 92%